Analysis of Work Posture and Risk of Musculoskeletal Complaints of Loading-Unloading Workers Using the REBA Method at PT. XYZ - Nadila, Febia Elsa; Suryadi, Akmal (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
PT XYZ is an airport manager in Indonesia engaged in the business of development, trade and services, and genuine estate. In the manual transportation of goods, extreme positions are still carried out. So that complaints of pain appear in several parts of the body, such as the neck, back, upper arms, and legs. The purpose of this study was to determine musculoskeletal complaints and analyze the work posture of workers. Risk assessment using the Rapid Entire Body Assessment (REBA) method because it can provide a more detailed evaluation of the level of risk of work posture as a whole. Based on the results of risk assessment research using the REBA method, workers in the Loading-Unloading Apron Area squatting position get a work posture risk value of 9, and the Apron Area standing position gets a work posture risk value of 8, where the value includes action level 4. For workers in the Loading-Unloading Makeup Area, the bending position gets a work posture risk value of 11, where the value consists of action level 4. Suggestions for improvement that can be proposed are making changes to the position of work postures and designing assistive devices.